O efeito dos marcadores externos na marcha de indivíduos com doença de Parkinson . - Patricia Rocha de Brito (2008)
To investigate the effect of visual (VC), auditory (AC) and the association of both cues (VAC) during gait in Parkinsons disease (PD) subjects in ON. METHODS: The design was a repeated measures study. Data was obtained using the movement analysis system Qualysis Pro-reflex. The General Linear Model, the Generalized Estimating Equations Model and multiple comparisons with Bonferroni were used in the analysis. The significance level was p<0.05. RESULTS: Ten PD subjects, male and female, participated in the study. Velocity and stride length increased in all conditions when compared to no-cue condition; AC increased cadence and VC decreased cadence; the percentage of the stance phase decreased in VC and VAC (p<0.02). During initial contact, AC generated the smallest plantar-flexion angle and in all cueing conditions the hip flexion angle increased (p<0.04). During weight acceptance, VC and VAC increased the plantar-flexion angle while AC decreased the angle (p<0.01). During terminal stance, VC and VAC generated higher dorsiflexion angle (p<0.01). The hip extension angle was elevated in all cueing conditions (p<0.01), with the highest extension occurring with VAC, followed by VC. During preswing, VAC generated the highest plantar-flexion angle and VC the highest hip extension angle, followed by VAC (p<0.01). During terminal swing, AC and VC generated less plantar flexion angle, VC and VAC less knee flexion angle and all cueing conditions generated higher hip flexion angle (p<0.01). CONCLUSION: All cueing conditions compared to walking with no-cue improved the gait pattern of the PD subjects. However, VAC condition showed better results.